Ceramika malowana z wczesnej epoki żelaza vs. nowożytna ceramika biała. Rozważania o magii i o „odczarowaniu świata” - Markiewicz, Małgorzata (Folia Praehistorica Posnaniensia, 2022)
The article contrasts two chronologically distinct groups of artifacts: painted ceramics from the Hallstatt period and the so-called white ceramics, produced until the end of modernity. They are related by means of the technique of covering a bright surface with colorful patterns and the stylistic similarity of certain geometric motifs. However, the ideas behind creating these pictorial representations were completely different. In the article, painted vessels from the Hallstatt period and modernity will be the starting point for detailed studies on magical and rational thinking about the world. It was in the Renaissance that, according to the concept of the sociologist and philosopher Max Weber (1864‒1920), a “disenchantment of the world”, took place ‒ e.g. the departure from the magical understanding of reality. Early Iron Age and Modernity ceramics will illustrate this process.